2018
DOI: 10.3343/alm.2018.38.2.102
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing Incidence of Listeriosis and Infection-associated Clinical Outcomes

Abstract: BackgroundListeriosis caused by Listeria monocytogenes has a high case-fatality rate (CFR) of approximately 20% to 30%. An increasing incidence of listeriosis has been reported in many countries recently. We investigated the annual incidence, clinical characteristics, and outcomes of listeriosis at three different hospitals in Korea and evaluated the effects of appropriate empiric antimicrobial treatments on patient outcomes.MethodsWe retrospectively collected the data of all culture-positive cases of human li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 30 publications
0
30
2
2
Order By: Relevance
“…In addition to bacteremia and CNS infection, Listeria can also lead to focal infections such as pneumonia, enteritis, and ophthalmitis (Marsaudon et al, 2018;Wan and Dong, 2015;Zhu et al, 2012). In the present study, the average age of non-UD patients was relatively younger than has been reported in other countries (Charlier et al, 2017;Choi et al, 2018). The reason for this may be that elderly people in China prefer to eat well-cooked food rather than raw or half-raw food.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In addition to bacteremia and CNS infection, Listeria can also lead to focal infections such as pneumonia, enteritis, and ophthalmitis (Marsaudon et al, 2018;Wan and Dong, 2015;Zhu et al, 2012). In the present study, the average age of non-UD patients was relatively younger than has been reported in other countries (Charlier et al, 2017;Choi et al, 2018). The reason for this may be that elderly people in China prefer to eat well-cooked food rather than raw or half-raw food.…”
Section: Discussioncontrasting
confidence: 55%
“…The present study and that of Feng et al (2013) report listeriosis in mainland China; however, the cases in the present study were reported during the years 2011-2017, while those in the study of Feng et al were reported during the years 1964Feng et al were reported during the years -2010, and more UD patients were reported in the present study (110/163 vs. 49/70). Similarly, an increase in the number of patients with listeriosis in Korea has also been reported over the past 10 years (Choi et al, 2018), with the elderly and the immunocompromised as the patients most involved. Improvements in methods of tracing Listeria infections (Moura et al, 2016;Jackson et al, 2016), increased awareness of listeriosis among clinicians, and the greater number of databases searched in the present study may have contributed to this increase in number of cases; however, it is speculated that the number of cases of listeriosis in mainland China may have been underestimated previously.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Invasive forms of listeriosis can lead to infection of CNS, in these cases even though the adequate antibiotic treatment the overall mortality rates remains nearly 30% [3]. The clinical manifestations of LMM are usually uncharacteristic, thus hindering prompt diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the incidence of listeriosis has increased in many countries [5]. However, the diagnosis of listeriosis in pregnant women is difficult because the symptoms are often ambiguous.…”
Section: Introductionmentioning
confidence: 99%